2017
DOI: 10.22616/erdev2017.16.n074
|View full text |Cite
|
Sign up to set email alerts
|

The impact of multifunctional biodiesel fuel additive on diesel engine combustion process

Abstract: Abstract. The use of fuel additives in engine fuels is a widespread tendency, and one which occurs on a worldwide basis. The most common area in the development of additives is for petrol and diesel fuel. The manufacturers claim that additives emulsify condensation water in the fuel tank, cleaning the fuel supply system and decreasing fuel consumption by improving the engine combustion process. Several additives have been developed for biofuels such as, for example, Valvoline VPS HD Diesel System Complete, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Therefore, the experimental conditions of operation to obtain a selective process that results in a high proportion of MG in the final FAME mixture, not only are much softer, but also there is no need to perform any additional purification operation, since glycerol is not produced, and the unreacted alcohol can be left as part of the mixture that constitutes the biofuel, so that the atomic efficiency of the process is practically 100% because all reagents are integrated in the final biofuel. Furthermore, in recent researches, it has been demonstrated that MG enhance the biodiesel lubricity as well [287][288][289][290][291][292][293][294][295].…”
Section: Biodiesel-like Biofuels That Integrate Glycerol As Monoglycementioning
confidence: 99%
“…Therefore, the experimental conditions of operation to obtain a selective process that results in a high proportion of MG in the final FAME mixture, not only are much softer, but also there is no need to perform any additional purification operation, since glycerol is not produced, and the unreacted alcohol can be left as part of the mixture that constitutes the biofuel, so that the atomic efficiency of the process is practically 100% because all reagents are integrated in the final biofuel. Furthermore, in recent researches, it has been demonstrated that MG enhance the biodiesel lubricity as well [287][288][289][290][291][292][293][294][295].…”
Section: Biodiesel-like Biofuels That Integrate Glycerol As Monoglycementioning
confidence: 99%
“…Whereas, BSFC values at 100% load for E10, E20, E30 and E40 for CR 9 are found to be 0.231, 0.239, 0.209 and 0.217 kg/h kW respectively. As compared with gasoline-air mixture, ethanol-gasoline-air mixture requires less amount of air to form stoichiometric fuel air mixture as a result, BSFC increase with ethanol gasoline blends 18 .…”
Section: Influence Of Ethanol On Performance Characteristics Of Enginementioning
confidence: 99%